GRAPHICAL USER INTERFACE DEVELOPMENT PROBLEM DESCRIPTION AND SOLUTIONS - Škapars, Arturs; Laduševs, Aigars; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
This article is about graphical user interface development problem description and possible solution summary. The goal of this work is to delve into specifics of common graphical user interface development problems and controversies, and list possible solutions that can be used to overcome.